UGCG promotes chemoresistance and breast cancer progression via NF-κB and Wnt/β-catenin pathway activation - Li Long; Lei Wang; Yiran Liang; Fangzhou Ye; Yuhan Jin; Dan Luo; Xiaoyan Li; Yajie Wang; Yaming Li; Dianwen Han; Bing Chen; Wenjing Zhao; et al. (Translational Oncology)
Background: Taxane-based chemotherapy is the primary treatment for triple-negative breast cancer (TNBC), yet clinical outcomes remain unsatisfactory due to the persistence of chemoresistance. Identifying key factors that contribute to chemoresistance and understanding the associated molecular mechanisms is therefore essential. Method: The GEO databases were utilized to pinpoint factors related to chemoresistance, which were subsequently validated using clinical tissue samples. The role of UGCG in the malignant progression and chemoresistance of TNBC was assessed through various functional assays. Western blotting, qRT-PCR, and immunohistochemistry were employed to investigate the signaling pathways associated with UGCG in TNBC. Results: UGCG expression was notably elevated in chemoresistant breast cancer tissues and cells, as identified in GEO databases and confirmed through immunohistochemistry. Additionally, findings from our cohorts indicated that higher levels of UGCG expression correlated with a lower rate of pathological complete response (pCR), suggesting it could serve as an independent predictor of chemotherapy effectiveness. Gain- and loss-of-function experiments demonstrated that UGCG enhanced the proliferation, metastasis, and stemness of breast cancer cells. Furthermore, treatment with paclitaxel or docetaxel resulted in increased UGCG expression, which in turn reduced chemotherapy-induced cell apoptosis and improved drug resistance and metastatic capabilities. Mechanistically, UGCG was found to amplify the activation of NF-κB and Wnt/β-catenin pathways, and the use of inhibitors targeting these pathways diminished the UGCG-induced malignant effects. Conclusion: Our findings underscore the significant role of UGCG in the chemoresistance and progression of breast cancer, suggesting it as a predictive biomarker and potential therapeutic target to combat chemoresistance in this disease.